Iron deficiency and iron deficiency anemia in pregnancy - Malinowski, A. Kinga; Murji, Ally (Canadian Medical Association journal (CMAJ), 2021)
Malinowski and Murji present several facts about iron deficiency and iron deficiency anemia. Iron deficiency and iron deficiency anemia are common during pregnancy and are associated with adverse outcomes. Prenatal iron deficiency occurs in more than 30% of pregnancies in Canada. It has been linked with low birth weight, small for gestational age size, preterm birth, need for blood transfusion for the mother, postpartum hemorrhage and long-term neurocognitive effects in childhood.